Modeling of a Wall and Reaction Slab for Quasi-Static Tests Using the Finite Element Method - Morillo Valencia, Andreina Rosa (2024)
To perform quasi-static tests on structural elements, reaction systems comprising slabs and walls are employed. This research aimed to assess the current state of a structure equipped with a reaction system composed of an "L"-shaped slab and wall. Computational programs were utilized for its evaluation, and the mechanical properties of the materials included in the mathematical model were derived from experimental tests. The results obtained indicate that the current capacity of the structure exceeds the demand. Additionally, the maximum load-bearing capacity of the reaction system was determined. Based on the verification of the existing structure, a design proposal is put forth for expanding the reaction wall with a maximum capacity of 490 [kN] and for the CIV infrastructure with an approximate area of 400 [m²]. This will contribute significantly to the advancement of scientific knowledge for the benefit of society.